2023
DOI: 10.1101/2023.10.25.564052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noradrenergic alpha-2a Receptor Stimulation Enhances Prediction Error Signaling in Anterior Cingulate Cortex and Striatum

Seyed A. Hassani,
Thilo Womelsdorf

Abstract: The noradrenergic system is implicated to support behavioral flexibility by increasing exploration during periods of uncertainty and by enhancing working memory for goal-relevant stimuli. Possible sources mediating these pro-cognitive effects are alpha-2A adrenoceptors in prefrontal cortex or the anterior cingulate cortex facilitating fronto-striatal learning processes. We tested this hypothesis by selectively stimulating alpha-2ARs using Guanfacine during feature-based attentional set shifting in nonhuman pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…A human brain mapping study that considered brainstem structures showed that the ACC had the strongest summed functional connectivity to all brainstem nuclei, making it a primary hub for cortical-brainstem functional connectivity (Hansen et al, 2023). Stimulation of alpha-2a adrenergic receptors in nonhuman primates was reported to increase the encoding of negative prediction errors in the ACC, linking the noradrenergic system to the ACC's involvement in learning (Hassani & Womelsdorf, 2023). Our lab has also shown the importance of reciprocal connections between the ACC and LC in affective responses to contextual novelty (Lustberg, Iannitelli, et al, 2020;.…”
Section: Lc Stimulation and The Global Signalmentioning
confidence: 99%
“…A human brain mapping study that considered brainstem structures showed that the ACC had the strongest summed functional connectivity to all brainstem nuclei, making it a primary hub for cortical-brainstem functional connectivity (Hansen et al, 2023). Stimulation of alpha-2a adrenergic receptors in nonhuman primates was reported to increase the encoding of negative prediction errors in the ACC, linking the noradrenergic system to the ACC's involvement in learning (Hassani & Womelsdorf, 2023). Our lab has also shown the importance of reciprocal connections between the ACC and LC in affective responses to contextual novelty (Lustberg, Iannitelli, et al, 2020;.…”
Section: Lc Stimulation and The Global Signalmentioning
confidence: 99%